Production of novel antimicrobial peptide human beta defensin 9 and its efficacy against common eye pathogenic bacteria in different salt concentration - Ab Hamid, Nurul Atikah (2018)
Beta defensins are small cationic peptide secreted by the surface epithelium in response to microbial threat. The human beta-defensin 9 (hBD9) is a relatively new defensin and its role as antimicrobial agent has not been described previously. In this study, Escherichia coli Mach 1 and E.coli BL21 (DE3) were used as cloning and protein expression hosts respectively. HBD9 gene was fused to a protein expression vector using the small ubiquitin-related modifier (SUMO) fusion system. The soluble hBD9-SUMO fusion protein expressed was purified by Ni-IDA immobolised metal affinity chromatography (IMAC) and SUMO was removed by SUMO protease. This study defined the novel antimicrobial peptide hBD9 and its efficacy against common Gram-positive and negative bacteria. Staphylococcus aureus and Pseudomonas aeruginosa were chosen because they are common bacteria that causing eye infection. The Minimal inhibitory concentration (MIC) and Minimal bactericidal concentration (MBC) of the hBD9 were determined for these microbes. Interestingly, hBD9 showed antimicrobial activity against Staphylococcus aureus but not Pseudomonas aeruginosa. Salt sensitivity and cationic concentration were tested by incubation with NaCl and MgCl2 using liquid culture containing hBD9 to analyse the effects of NaCl and MgCl2 concentration on the antimicrobial activity. Antimicrobial activity against Staphylococcus aureus of hBD9 was not supressed by NaCl and MgCl2. All the antimicrobial property of the hBD9 protein against the common bacteria was verified by using conventional methods. The results improved the current knowledge on the hBD9 and its antimicrobial properties. This will drive towards the discovery of a broad spectrum, safe by effective resistant-free antibiotic in the future. The finding of this study can be used as a reference in the future investigation and it might benefits scientific community to better by others scientist or researchers to increase understanding and find new effective antibiotics.